RELIGIÃO E ESPORTE: OS ATLETAS RELIGIOSOS E A RELIGIÃO DOS ATLETAS UM ESTUDO DAS TRANSFORMAÇÕES DA RELAÇÃO ENTRE O SUB-CAMPO PROTESTANTE BRASILEIRO E O ESPORTE - Aguiar, Reinaldo Olecio (2004)
Research of Religion Sociology that looks to present the transformation of the relationship between the Brazilian Protestant sub-field and the sport, especially the soccer, through bibliographical, historical and field surveys. It intends to demonstrate that the gradual acceptance of the soccer in the Protestant means was consequence of the progress of the secularization process happened in the Brazilian society during the 20th century. It was also consequence of the gradual disenchantment of the Protestant sub-field. It contributed to that process the turn of sacred time, Sunday, in regular time, what demonstrates a transformation of the Protestant weltanschauung. The increasing professionalization of the soccer more and more accept as a legitimate activity for the Brazilian Protestants also contributed to your acceptance. The investigation brings a case study, that presents and analyzes the group that call themselves Atletas de Cristo , example of the transformation as much of the Protestant religious sub-field in your relationship with the sport, as much as transformations of the sporting field. To understand the religion of Atletas de Cristo , it developed the group ethnography, the analysis of your own literature, your relationships with atletas-não-de-Cristo , as well as your sacred understanding of the sport.(AU)